Tax Aggressiveness, Capital Structure, Corporate Governance Dan Firm Performance - Ali Hardana Hardana; Lismawati Hasibuan; Sulaiman Efendi Hasibuan (CV. AFDIFAL MAJU BERKAH, 2023)
Based on agency theory, the purpose of this study is to test empirically the effect of tax aggressiveness, capital structure and corporate governance on firm performance. Multiple regression analysis was used to analyze three years of data (2017-2021) in the unit sample, to find the effect of tax aggressiveness, capital structure, corporate governance on firm performance. The results of the study found that tax aggressiveness has a positive effect on company performance, but corporate governance mechanisms must work effectively, so as to reduce agency costs. And the joint influence of tax aggressiveness, capital structure, governance on company performance. The findings of this study provide practical implications that the importance of strengthening corporate governance mechanisms in order to improve company performance and reduce agency costs within the company.